Current Status of Immobilization Techniques for Geological Disposal of Radioactive Iodine in Japan. Issue 1744 (2015) - Idemitsu, Kazuya; Sakuragi, Tomofumi
ABSTRACT: Nuclear reprocessing plants in Japan produce radioactive iodine-bearing materials such as spent silver adsorbents. Japanese disposal plans classify radioactive waste containing a given quantity of iodine-129 as Transuranic Waste Group 1 for spent silver adsorbent or as Group 3 for bitumen-solidified waste, and stipulate that such waste must be disposed of by burial deep underground. Given the long half-life of iodine-129 of 15.7 million years, it is difficult to prevent release of iodine-129 from the waste into the surrounding environment in the long term. Moreover, because ionic iodine is soluble and not readily adsorbed, its migration is not significantly retarded by engineered or natural barriers. The release of iodine-129 from nuclear waste therefore must be restricted to permit reliable safety assessment; this technique is called "controlled release". It is desirable that the release period for iodine be longer than 100, 000 years. To this end, several techniques for immobilization of iodine have been developed; three leading techniques are the use of synthetic rock (alumina matrix solidification), BPI (BiPbO2 I) glass, and high-performance cement. Iodine is fixed as AgI in the grain boundary of corundum or quartz through hot isostatic pressing in synthetic rock, as BPI in boron/lead-based glass, or as cement minerals such as ettringite in high-performance alumina cement. These techniques are assessed by three models: the corrosion model, the leaching model, and the solubility-equilibrium model. This paper describes the current status of these three techniques.